2022
DOI: 10.1186/s12989-022-00496-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential involvement of inhaled iron (Fe) in the neurotoxic effects of ultrafine particulate matter air pollution exposure on brain development in mice

Abstract: Background Air pollution has been associated with neurodevelopmental disorders in epidemiological studies. In our studies in mice, developmental exposures to ambient ultrafine particulate (UFP) matter either postnatally or gestationally results in neurotoxic consequences that include brain metal dyshomeostasis, including significant increases in brain Fe. Since Fe is redox active and neurotoxic to brain in excess, this study examined the extent to which postnatal Fe inhalation exposure, might c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…In perspective, our further efforts will be focused on analysis of changes in mitochondria functioning in response to application of smoke preparations from different types of organics. Also, further experiments using in vivo animal models, inhalation approaches and new technique 45 47 are necessary to uncover detailed mechanisms of MPs action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In perspective, our further efforts will be focused on analysis of changes in mitochondria functioning in response to application of smoke preparations from different types of organics. Also, further experiments using in vivo animal models, inhalation approaches and new technique 45 47 are necessary to uncover detailed mechanisms of MPs action.…”
Section: Discussionmentioning
confidence: 99%
“…Despite utilization problems, plastic is currently used to produce many products because of its low cost, light weight, and high durability and is emerging as the dominant material causing marine pollution 51 , 53 55 . It should be noted that PM can be neurotoxic itself and also due to adsorption of neurotoxic environmental components, in particular heavy metals 45 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The uncommon nanoscale sizes, which are not familiar to biological systems can cause detrimental effects on human health. Sobolewski et al confirmed the Fe 2 O 3 nanoparticles with sizes between 11.2 and 13.6 nm can lead to oxidative damage and neurotoxicity in the mouse brain [ 189 ]. Meanwhile, the rapid clearance of SiNPs from blood depletes plasma apolipoprotein A-I and facilitates atherosclerosis [ 190 ].…”
Section: Reviewmentioning
confidence: 99%
“…158 Meanwhile, in vitro, results showed that exposure to SiO 2 -NPs decreased cell viability, increased lactate dehydrogenase levels, triggered oxidative stress, disrupted the cell cycle, induced apoptosis, and activated p53-mediated signaling pathways. 159 Sobolewski et al 160 showed that exposure to Fe 2 O 3 -NPs caused oxidative damage and neurotoxicity in the mouse brain. In addition to the above-mentioned NPs, NPs such as Ag-NPs, 161,162 PbO-NPs, 163 and ZnO-NPs 164 can cause damage to the nervous system to vary degrees.…”
Section: Toxic Effects Of Nps On the Nervous Systemmentioning
confidence: 99%